1994
DOI: 10.1159/000126638
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Angiotensin-II-Induced Prolactin Release in vivo and in vitro in Female and Male Rats

Abstract: The prolactin-releasing effect of angiotensin II (AII) was studied in the developing female and male rat in vivo and in vitro. AII (50 and 100 µg/100 g b.w.) was injected intraperitoneally to female and male rats aged 4, 12, 20 and 28 days and males aged 38 days. AII (10–6M) was also tested in pituitaries incubated in vitro from animals of both sexes aged 12, 20 and 28 days. In addition, as two subtypes of AII receptors have been characterized on the basis of displacement with specific AII antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…It is well known that the sympathetic nerve might stimulate the juxtaglomerular cells in the kidney to release renin which, in turn, elevates the level of angiotensin II in plasma (48,49). Circulating angiotensin II has been described to stimulate prolactin secretion (12) and its potency in stimulating prolactin release from pituitary cells in vitro is one of the highest among potential prolactin-releasing factors (1). Therefore, during hemorrhage the increased circulating angiotensin II acting on pituitary lactotrophs and circulating catecholamines acting on the PO/AH may facilitate prolactin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the sympathetic nerve might stimulate the juxtaglomerular cells in the kidney to release renin which, in turn, elevates the level of angiotensin II in plasma (48,49). Circulating angiotensin II has been described to stimulate prolactin secretion (12) and its potency in stimulating prolactin release from pituitary cells in vitro is one of the highest among potential prolactin-releasing factors (1). Therefore, during hemorrhage the increased circulating angiotensin II acting on pituitary lactotrophs and circulating catecholamines acting on the PO/AH may facilitate prolactin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study has shown that the angiotensin II receptor AT 1A is predominantly expressed in the rat forebrain and that, in contrast, the angiotensin II receptor AT 1B subtype predominates in the anterior (21). Although the possibility that angiotensin II functions as a hormone influencing prolactin secretion in certain physiological conditions has been proposed (10,12,13,16,17,21,22) experimental data have not been present. Recently, it has been found that in vivo stimulation of prolactin release by peripherally injected angiotensin II increases with age, and first responses were observed at 20 days of age in both sexes in rats (12).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous observations indicate that Ang II can contribute to the physiologic regulation of prolactin secretion (Freeman et al 2000), and that it releases prolactin both in vivo and in vitro (Diaz-Torga et al 1994. Angiotensin II receptors, which mediate prolactin secretion (AT1), belong to the family of G protein-coupled receptors.…”
mentioning
confidence: 99%
“…The anterior pituitary predominantly expresses the AT1B isoform of the AT1 receptor (31,41), with a low expression of the AT1A isoform and the AT2 receptor subtype (41,45). ANG II releases prolactin both in vivo and in vitro (14) and activates extracellular signal-related kinase 1/2 through a calcium-dependent, AT1 receptor-specific mechanism (47). Yet, participation of AT2 receptors in ANG II effects on pituitary function has not been described to date.…”
mentioning
confidence: 99%